Acaricidal activity of Furcraea foetida leaf extract against engorged female Rhipicephalus (Boophilus) microplus ticks (Bioscience Journal, 2021)
The Rhipicephalus (Boophilus) microplus tick is a major concern for the livestock market worldwide, as it causes serious economic damage. Plant-derived acaricides are an attractive alternative to control this ectoparasite and limit the development of resistance. Therefore, the aim of this study was to evaluate the acaricidal activity of Furcraea foetida leaf extract against engorged female R. (B.) microplus ticks. Our in vitro bioassays showed that the crude extract of leaves from F. foetida caused hemorrhagic swelling and skin lesions in the ticks, and three days of treatment caused 100% mortality. Dose-response assay indicated that this toxicity effect was dose-dependent. Similar effects were observed when the crude extract from F. foetida leaves was denatured by boiling at 100°C. These results suggest that the toxicity of the leaf extract might be associated with thermostable biomolecules. Together, our results show for the first time that the crude extract of F. foetida leaves has acaricidal activity against engorged female R. (B.) microplus ticks and it acts in a dose-dependent manner.